Filmes delgados luminescentes obtidos a partir de hidroxicarbonatos de ítrio ativados por európio ou térbio - Niyama, Emy [UNESP]; Alencar, Anselmo Colombo de [UNESP]; Vila, Ligia Delgado da [UNESP]; Stucchi, Elizabeth Berwerth [UNESP]; Davolos, Marian Rosaly [UNESP] (Sociedade Brasileira de Química, 2004)
These films were obtained by dip coating. Parameters like dislocation velocity; number of deposits, suspension concentration, and number of deposits followed or not by heat treatment between each deposit and calcination temperature were evaluated for establishing the best homogeneity. The obtained films were characterized in terms of their morphology, optical quality and photoluminescence by scanning electron microscopy (SEM), UV-vis absorption spectrophotometry and luminescence spectroscopy, respectively. The morphologic and luminescent characteristics showed dip coating as good laboratory technique for development of thin films for optical applications.
Luminescent thin films obtained from ytrium hydroxycarbonates activated by terbium or europium
Keywords: thin film; dip coating; sol-gel